Clinical and morphological features of malformations of the mitral valve complex - Е. Trysvetova; O. Yudina (Российский кардиологический журнал)
The mitral valve complex is a multicomponent anatomically and functionally coordinated formation, ensuring the activity of the left ventricle and, in general, the heart. Congenital disorders of the structure, quantity, and form of the mitral complex components can be asymptomatic or cause hemodynamic changes that require surgery. Often, clinical signs of mitral complex abnormalities are manifested as mitral stenosis, regurgitation or its combination and contribute to misdiagnosis. To identify the morphological features of abnormalities by echocardiography, it is necessary to know the possible structure aberrations. The article describes the normal anatomy of the mitral valve complex and abnormalities of the fibrous ring, valve leaflets, papillary muscles and chordae tendineae.